Effects of soot inception and condensation PAH species and fuel preheating on soot formation modeling in laminar coflow CH4/air diffusion flames doped with n-heptane/toluene mixtures. (1st October 2019) - Zhang, Cuiqi; Chen, Longfei; Ding, Shuiting; Xu, Huanhuan; Li, Guangze; Consalvi, Jean-Louis; Liu, Fengshan
Abstract: This paper investigates the effects of soot inception and condensation polycyclic aromatic hydrocarbon (PAH) species and fuel preheating on soot prediction in 2D coflow laminar CH4 /air diffusion flames doped with vaporized gasoline surrogate fuels, i.e., n- heptane/toluene mixtures. To evaluate the importance of considering multiple PAHs in soot inception and condensation and fuel pyrolysis near fuel tube outlet in the prediction of soot distribution along the flame centerline, the pyrene-based soot inception and PAH condensation model was improved by considering multi-PAH (A2, A2 R5, A3 C2 H, A4, BGHIF) as nucleation and condensation species. The fuel preheating effect upstream the fuel tube exit was taken into account. Inclusion of multiple PAHs in soot inception and condensation leads to greatly enhanced soot formation along the flame centerline region due to enhanced soot inception and surface growth via PAH condensation. As a result of soot inception through smaller PAH (A2 ), soot appears at a lower flame height above the burner exit than experiments. The fuel preheating effect causes significantly higher fuel stream temperatures in the near burner wall region and appreciable fuel pyrolysis. Soot inception is further enhanced by the fuel preheating effect and soot appears at an even lower height above the burner exit with a reduced flame height. This study demonstrated that both multi-PAH coagulation and fuel preheating strengthen soot inception and improve the predicted soot volume fractions along the flame centerline, but they are still insufficient to achieve good agreement with available experiments. Plausible ways to further improve the soot model are discussed.